Bimetallic Aerogels: High‐Performance Electrocatalysts for the Oxygen Reduction Reaction1. Issue 37 (22nd July 2013) - Liu, Wei; Rodriguez, Paramaconi; Borchardt, Lars; Foelske, Annette; Yuan, Jipei; Herrmann, Anne‐Kristin; Geiger, Dorin; Zheng, Zhikun; Kaskel, Stefan; Gaponik, Nikolai; Kötz, Rüdiger; Schmidt, Thomas J.; et al.
<x xml:space="preserve">Abstract</x> Best of both worlds: PtxPdy, Pt, and Pd aerogels with high surface area and porosity can be synthesized in a controlled fashion by a straightforward and environmentally benign strategy. These materials, which are highly active and stable catalysts for the oxygen reduction reaction in PEFC cathodes, combine the high stability of extended surfaces with the high surface area of nanoparticles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>